Extracurricular Study of Qira'atul Qutub in the Formation of Students' Religious Character at SMPI Darul Ulum Probolinggo - Zaka, Muhammad Zakaria; Nuha, Nazahah Ulin (FALASIFA : Jurnal Studi Keislaman, 2025)
This study explores the role of the Qira'atul Qutub extracurricular program in the formation of students' religious character at SMPI Darul Ulum Probolinggo through book reading activities. Research methods include observation, semi-structured interviews, and documentation. The results show that this program helps to classify classes and implement various support programs. The supporting factors include the role of educators, student motivation, and the school's vision and mission, while the inhibiting factors include educators' unpunctuality, lack of student motivation, and reduced lesson hours. The achievement of students' religious character includes reading and murojaah of the yellow book, obedience to time, polite behavior, and obedience to parents and educators. The implication is that this activity is important in developing the religious character of students at SMPI Darul Ulum Probolinggo, showing that religious character can be formed through Qira'atul Qutub by deepening religious understanding and shaping students' morals, discipline, and responsibility.